Preparation of quality drinking water as a basis of the environmental safety and human health - Kravchenko, Maryna (Publishing House of Lviv Polytechnic National University, 2016)
The problem of drinking water preparation with specified quantitative and qualitative composition is very acute today in various countries including Ukraine. The consequences of using the method of reverse osmosis at tap water purification using the equipment with the membrane element Filmtec XLE 440 (8"), produced by DOW Chemical (USA), have been reviewed. Positive characteristics as well as economical and technological shortcomings of reverse osmosis equipment have been proved.
Keywords: drinking water; reverse osmosis; preparation of potable water